In Malang, Indonesia, a techno-economic analysis of hybrid energy systems in public buildings - Mochammad Junus; Marjono Marjono; Aulanni’am Aulanni’am; Slamet Wahyudi (Bulletin of Electrical Engineering and Informatics, 2022)
Because of the fickle nature of the renewable sources of energy production, professionals in this sector have developed hybrid renewable energy systems (HRES) that offer a constant and stable load supply. This research intends to build off-grid hybrid energy systems (HES) in Malang, Indonesia, that uses a solar generator, wind turbine, and biogas to power public buildings. The HOMER program was used to construct this model. Following the computations, multiple hybrid renewable energy system models are used to analyze each component’s capital cost and also cost of energy (COE). Furthermore, energy output, gas emissions, and a thermoeconomic assessment of several HRES models have been explored. Two ideal HRES models were evaluated: one with a biogas generator and one without. According to the research, employing a generator of biogas would reduce fuel consumption and emissions by 68.3%. This HRES model is impressive in light of Malang’s severe air pollution. Switching from diesel to biogas generator decreases NPC by 6.84%, according to the data.